ANALYTICAL AND EXPERIMENTAL DETERMINATION OF CARRYING CAPACITY OF THE CARCASS ELEMENTS OF STADIUM “VORSKLA” NAMED AFTER ALEXEY BUTOVSKY (POLTAVA) - Горик, О. В.; Ковальчук, С. Б.; Яхін, С. В. (Scientific Progress & Innovations, 2014)
Results of modelling of a spatial work of elements of engineering designs taking into account available restrictions of deformation of crossbars on the basis of natural examination and test of separate inclined crossbars of the frames of a tribune construction of stadium (East tribune) are presented. Modelling has given the chance to establish real conditions of their work and to define an operational resource. Researches are based on use of ratios of iterative shift model of a bend of composite bars in the conditions of limited deformation. As a result of the carried-out mathematical modelling level of margin of safety of inclined crossbars within standard useful loading that has allowed drawing the conclusion about possibility of reliable operation by a construction tribune has been defined.